2021
DOI: 10.3390/ma14154311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mold and Heat Transfer Fluid Materials on the Temperature Distribution of Large Framed Molds in Autoclave Process

Abstract: Massive composite components manufactured by autoclave curing in large framed molds are extensively used in the aerospace industry. The high temperature performance of the large framed mold is the key to achieving the desired composite part quality. This paper explores and summarizes the important thermal properties of metal and heat transfer fluid materials influencing the heating performance of large framed molds, with the aim of improving the mold temperature distribution. Considering the fluid–thermal–soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, some researchers also investigated the influence of different mold materials selection on the temperature. Zhang et al [ 10 ] used a CFD model to study the influence of two materials, copper and steel, on the temperature of large-framed molds. They found that using copper as the mold material can significantly improve the temperature uniformity of the mold.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some researchers also investigated the influence of different mold materials selection on the temperature. Zhang et al [ 10 ] used a CFD model to study the influence of two materials, copper and steel, on the temperature of large-framed molds. They found that using copper as the mold material can significantly improve the temperature uniformity of the mold.…”
Section: Introductionmentioning
confidence: 99%
“…Thermosetting composites have been widely used in aerospace, automotive, civil engineering, and other fields due to their light weights, high specific strength, fatigue resistance, and strong designability [1][2][3][4]. The composites are usually produced by an autoclave with a determined cure cycle profile in order to initiate and sustain an irreversible cross-linking of the resin [5][6][7][8]. With the composite increasingly used in complex structures, the thickness would exceed the applicable range of curing parameters recommended by Manufacturer Recommended Cure Cycles (MRCC) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [9,10] developed an optimization process combining numerical simulations with a greedy genetic algorithm to realize the optimal layout and geometry of the local-isolation structure in molds, and nally, achieve a more uniform heating condition and more synchronous curing process. Zhang et al [11] developed a reliable CFD simulation model considering the uid-thermal-solid interaction inside the autoclave and used the single-variable method to study the e ects of the material thermal properties on the temperature performance of large framed molds.…”
Section: Introductionmentioning
confidence: 99%